2019
DOI: 10.2460/ajvr.80.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of focused cardiac ultrasonography for predicting fluid responsiveness in conscious, spontaneously breathing dogs

Abstract: OBJECTIVE To evaluate the diagnostic usefulness of focused cardiac ultrasonography and selected echocardiographic variables for predicting fluid responsiveness in conscious, spontaneously breathing dogs with various clinical conditions. ANIMALS 26 dogs (15 males and 11 females) with a median age of 84 months (range, 12 to 360 months) and median body weight of 8 kg (range, 2 to 35 kg) referred for various clinical conditions. PROCEDURES Left ventricular end-diastolic internal diameter normalized to body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 43 publications
1
28
2
Order By: Relevance
“…However, a prospective study in 25 hospitalized dogs found HR decreased significantly in both fluid responders and non-responders following a 4 ml/kg mini isotonic crystalloid bolus, suggesting HR could not differentiate between the two groups (16). Several other studies in spontaneously breathing and anesthetized dogs also found changes in HR failed to differentiate fluid responders and non-responders (15,19,28,32). These findings are similar to human ICU studies that also demonstrate the ability of a change in HR to predict fluid responsiveness is quite variable (62,63).…”
Section: Clinical Exam Findingsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, a prospective study in 25 hospitalized dogs found HR decreased significantly in both fluid responders and non-responders following a 4 ml/kg mini isotonic crystalloid bolus, suggesting HR could not differentiate between the two groups (16). Several other studies in spontaneously breathing and anesthetized dogs also found changes in HR failed to differentiate fluid responders and non-responders (15,19,28,32). These findings are similar to human ICU studies that also demonstrate the ability of a change in HR to predict fluid responsiveness is quite variable (62,63).…”
Section: Clinical Exam Findingsmentioning
confidence: 98%
“…Dynamic Markers below. In both the human and veterinary literature, the magnitude of change (increase or decrease) that constitutes a positive response varies from 6 to 36% depending on the physiologic parameter measured and conditions under which the preload challenge is induced (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In general, there is a trend to define a positive fluid responder as any patient that has an increase in a measured dynamic marker, such as CO, by ≥10-15% following a preload challenge (14,16,25,(28)(29)(30).…”
Section: Fluid Responsivenessmentioning
confidence: 99%
See 3 more Smart Citations